2015
DOI: 10.1007/s00404-015-3787-x
|View full text |Cite
|
Sign up to set email alerts
|

HPV-16 E6/E7 promotes cell migration and invasion in cervical cancer via regulating cadherin switch in vitro and in vivo

Abstract: Our results unraveled the possibility that HPV-16 E6/E7 could promote cell invasive potential via regulating cadherin switching, and consequently contribute to progression and metastasis of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…4a). These pathways are consistent with known biological activities of E7, which has been reported to regulate multiple genes to modulate translation 48 , promote cell migration 49 , play a role in macromolecular complex subunit organization 50 , DNA replication 51 and redox balancing 52 .
Figure 4Label-free mass spectrometry quantification of RPE1 vector and E7 expressing cells under hypoxia. ( a ) RPE1 vector and E7 expressing cells treated with 200 μM DFO were prepared for mass spectrometry.
…”
Section: Resultssupporting
confidence: 76%
“…4a). These pathways are consistent with known biological activities of E7, which has been reported to regulate multiple genes to modulate translation 48 , promote cell migration 49 , play a role in macromolecular complex subunit organization 50 , DNA replication 51 and redox balancing 52 .
Figure 4Label-free mass spectrometry quantification of RPE1 vector and E7 expressing cells under hypoxia. ( a ) RPE1 vector and E7 expressing cells treated with 200 μM DFO were prepared for mass spectrometry.
…”
Section: Resultssupporting
confidence: 76%
“…More importantly, cadherin switches (referred to as switches from E-cadherin to P-cadherin or E-cadherin to N-cadherin) have been regarded as key hallmarks of EMT [28] and to be involved in TGF-β signaling-induced EMT [29]. Previously, we found that aberrant E-cadherin expression led to increased migration and invasion of cervical SCC cells and could serve as a key biomarker for a poor prognosis of early-stage cervical SCC [7,8]. Furthermore, we found that P-cadherin could affect the expression of E-cadherin and p120 catenin, thereby contributing to cervical cancer initiation and progression [30].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we found that HPV-16 E6/E7 may regulate an E-P cadherin switch to promote cervical SCC cell growth and invasion [8].…”
Section: Hpv-16 E6/e7 Simultaneously Regulates Mir-34a and Wnt1 Exprementioning
confidence: 97%
See 1 more Smart Citation
“…Although similar permeable membrane insert systems have been employed for the study of secreted factors involved in viral infections, cancer biology, and immune cell migration [22][23][24][25][26] , few studies involving bacterial interactions with host cells have utilized this approach 6,27,28 . Even studies that have employed such systems to explore interactions between bacteria and host cells have primarily focused on migration of inflammatory cells or bacteria through an epithelial or endothelial monolayer plated on the permeable membrane insert.…”
Section: Introductionmentioning
confidence: 99%